ROMAN PERGAOELAN, PENULISAN SEJARAH, DAN KANONISASI SASTRA INDONESIA - Sudarmoko Sudarmoko (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
The history of Indonesian Literature mainly based on canonical works established by scholars and critics. In this condition, literary works published by private and periphery publishers are ignored from the history of Indonesian literature. This paper discusses a private publisher, Penjiaran Ilmoe (1938-42), which published a series of literary works called Roman Pergaoelan in correlation with the writing of the historyIndonesian literature. The discussion presented in this paper is based on the sociology of literature, exploring the extrinsic and intrinsic aspects of Roman Pergaoelan. The discussion is hoped to give a contribution in the development of writing the history of Indonesian literature by considering literary works published in out side centre of authority and categorized as popular or dime literature.